Comparative effect of organic manures and inorganic fertilizers on vegetative growth, ield and uality of Ber (Zizyphus mauritiana Lamk.) cv. Gola under Semi-arid conditions (Indian Journal of Arid Horticulture, 2017)
An experiment was carried out at S.K.N.A.U.,Jobner (Jaipur) Rajasthan to find out the comparative effect of organicmanures and inorganic fertilizers on growth parameters of three years old ber orchard cv. Gola. Four levels of organicmanures (control, FYM @ 20 kg/plant, Vermi- compost @ 6 kg/plant and poultry manure @ 8 kg/plant) and five levels ofRDF (control, 50% RDF, 75% RDF, 100% RDF and 125% RDF) in Randomized Block Design with three replications weretaken to provide balance fertilization of ber under semi-arid region of northern India during 2015-16. The experimentalresults revealed that application of Vermi-compost @ 6 kg/plant and 125% recommended dose of fertilizers significantlyinfluence the growth parameters (Plant height, plant spread (E-W and N-S), number of primary branches, average length ofprimary branch, number of secondary branches per primary branch and leaf area), fruit yield (kg/plant and q/ha) and fruitquality (TSS and acidity content) of experimental plants
Keywords: Organic manures; inorganic fertilizers; semi-arid conditions; vegetative growth; fruit yield and quality